The Transformation of Education in Islamic Civilization: From Classical Scientific Traditions to Modern Education Systems - Dede Fitriani; Achmad Maftuh Sujana; Raihan Rizky Ramadhan; Fina Najha Aini; Sultan Maulana Al-Muhtadin (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
Islamic education has a long history of shaping human civilization through the integration of spiritual, intellectual, and social values. Throughout history, the Islamic education system has undergone a significant transformation from classical scientific traditions centered in mosques, madrasahs, and pesantren, to modern systems that emphasize the balance between religious and scientific knowledge. This transformation involves not only methodological changes but also a reconstruction of Islamic epistemology to address the challenges of modern times, including the digital era and globalization. This study employs a qualitative literature review approach, analyzing contemporary academic works published between 2019-2025. Findings indicate that modern Islamic education emphasizes the integration of knowledge (unity of knowledge), the strengthening of digital literacy, and the development of spiritual character aimed at communal well-being. The transformation of education in Islamic civilization is both a historical necessity and a philosophical evolution that must continue to align with global developments.